KEANEKARAGAMAN JENIS NYAMUK Anopheles DI DAERAH DENGAN ATAU TANPA KEBUN SALAK DI KABUPATEN BANJARNEGARA - Dyah Widiastuti; Bambang Yunianto; Bina Ikawati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2006)
Anopheles has been known as vectors of malaria and filaria. A research which was aimed to evaluate the diversity of Anopheles mosquitoes at Salak and Non Salak Areas was conducted. This Research located in Banjarnegara Regency which lay in a mountainous in the middle of Central Java (7'12"- 7'31 N and 109'20"-109'45"W). The location was divided into two groups i.e. (1) Kendaga Village (Banjarmangu Subdistrict) representing of Salak area, (2) Badakarya Village (Punggelan Subdistrict) representing Non Salak area. Mosquitoes were collected by landing and resting collection methods. All mosquitoes were anaesthetized with chloroform and identified under microscope. Shanon-Weaver Index and Eveness Index were measured to evaluate the diversity of Anopheles mosquitoes. The results showed there were 6 species of Anopheles from both areas i.e. A. aconitus. A. balabacensis. A. barbirostris. A. kochi. A. vagus and A. maculatus. Result of examination by Independent Sample T-Test indicated that the diversity index value between two areas were not significantly different.